Foot-Transmitted Vibration: Automotive Accelerator Pedal-Pad Vibration on Tarmac and Paved Road - A. R., Yusoff; B. M., Deros; D. D. I., Daruis; E. H., Sukadarin (Society of Automotive Engineers Malaysia, 2019)
Vibration at the pedal-pad may contribute to the discomfort of the foot plantar fascia during driving. In this study, the experiment is conducted using a “five-time repeatability” test of the same procedure and shall determine root-mean-square vibration magnitude and vibration transmissibility on Z-axis or vertical vibration magnitude for the three different sizes of pedal-pad on tarmac and paved surface. ISO 2631-1:1997 is used for frequency-weighting (Wk) in one-third octave step with a range of frequency 0.5 Hz to 80 Hz in vertical vibration. The analysis is divided into two; frequency-weighted acceleration and frequency-weighted rootmean- square acceleration on vibration magnitude; and vibration transmissibility. The result shows that small pedal-pads at a resonance frequency of 4 Hz and 10 Hz give high value on frequency-weighted acceleration compared to medium and large sized pedal-pads. The frequency-weighted RMS acceleration on the tarmac and paved road surfaces show that small pedal-pad also give high value compared to medium and large sized pedal-pads. The International Roughness Index shows that paved road surfaces affect frequency-weighted RMS acceleration differently, which is higher compared with tarmac. The vibration transmissibility result shows that the percentage pedal-pad effective amplitude transmissibility value on paved road surfaces is more than 100% compared with the tarmac road surface on three sizes of pedalpads. A comparison of frequency-weighted RMS acceleration of pedalpads and car bodies for three different sizes of the pedal-pad also show that the paved road surface contributes more vibration to pedal-pads compared with the tarmac road surface. It can, therefore, be concluded that the size of the pedal-pads and the type of road surface can influence foot-transmitted vibration.